Sandbar Breaches Control of the Biogeochemistry of a Micro-Estuary - Suari, Yair; Amit, Tal; Gilboa, Merav; Sade, Tal; Krom, Michael D.; Gafny, Sarig; Topaz, Tom; Yahel, Gitai (Frontiers in Marine Science, 2019)
Micro-estuaries in semi-arid areas, despite their small size (shallow depth of few meters, length of few kilometers and a surface area of less than one square kilometer) are important ecosystem services providers. Despite their high abundance, tendency to suffer from eutrophication and vulnerability to other anthropogenic impacts, such systems are among the least studied water bodies in the world. In low tidal amplitude regions, micro-estuaries often have limited rate of sea-river water exchange, somewhat similar to fjord circulation, caused by a shallow sandbar forming at the coastline. The long-term study we report here was inspired by the idea that, due to their small size and low discharges regime, relatively small interventions can have large effects on micro-estuaries. We used a stationary array of sensors and monthly detailed water sampling to characterize the Alexander estuary, a typical micro-estuary in the S.E. Mediterranean, and to identify the main stress factors in this aquatic ecosystem. The Alexander stream is stratified throughout the year with median bottom salinity of 18 PSU. Prolonged periods of hypoxia were identified as the main stress factor. Those were alleviated by breaching of the sandbar at the estuary mouth by sea-waves or floods (mostly during winter) that flush the anoxic bottom water. Analysis of naturally occurring sandbar breaches, and an artificial breach experiment indicate that the current oxygen consumption rate of the Alexander micro-estuary is too high to consider sandbar breaches as a remedy for the anoxia. Nevertheless, it demonstrates and provides the tools to assess the feasibility of small-scale interventions to control micro-estuaries hydrology and biogeochemistry.